2012
DOI: 10.1248/bpb.b12-00150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Basophil CD203c as a Predictor of Carboplatin-Related Hypersensitivity Reaction in Patients with Gynecologic Cancer

Abstract: The incidence of hypersensitivity reaction (HR) to carboplatin has been reported to increase after repeated use of the drug. However, a reliable ex vivo test to predict HR to carboplatin is not currently available. We evaluated the clinical usefulness of measuring basophil CD203c to predict carboplatin-related HR in this prospective case-control study conducted at Mie University Hospital between October 2009 and September 2010. Eleven patients had history of carboplatin-related HR within the past 3 years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
(39 reference statements)
3
29
0
1
Order By: Relevance
“…Data analysis was performed by FlowJo (TreeStar, Ashland, OR, USA). BAT was considered positive when there was an SI ≥2 and/or a basophil activation percentage > 2% [16,17,[19][20][21]. We compared basophil activation percentage and SI (for CD63 and CD203c expression) between patients and controls.…”
Section: Cd203cmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis was performed by FlowJo (TreeStar, Ashland, OR, USA). BAT was considered positive when there was an SI ≥2 and/or a basophil activation percentage > 2% [16,17,[19][20][21]. We compared basophil activation percentage and SI (for CD63 and CD203c expression) between patients and controls.…”
Section: Cd203cmentioning
confidence: 99%
“…BAT has also been studied as a possible diagnostic method, given the role of basophils and mast cells as key cells in immediate hypersensitivity reactions. Viardot-Helmer et al [15] found an increased expression of CD63 with exposure to cisplatin; Iwamoto et al [16][17][18] and Jean-Luc [19] detected increased expression of the CD203C marker after incubation with carboplatin and oxaliplatin, respectively; Giavina-Bianchi et al [20] evaluated CD63 and CD203c expression in patients submitted to rapid drug desensitization (RDD) with oxaliplatin and carboplatin, obtaining positive results in 73% of patients. Due to the existing limitations of skin tests, further studies are essential to ascertain the role of the in vitro diagnostic methods, particularly BAT, in hypersensitivity reactions to platinum compounds, as well as to make comparisons with controls in order to gain a better understanding of the underlying immunological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the only 2 patients with positive IDT had simultaneously a positive BAT. In the literature, BAT exhibits a good sensitivity and an excellent specificity in the diagnosis of allergy to drugs (e.g., antibiotics or cytotoxic chemotherapy) [24,39,40], but data concerning BAT in the context of IHR to monoclonal antibodies are largely lacking [41,42]. In our study, 2 out of the 3 patients who had positive BAT successfully received subsequent IFX infusions after induction of tolerance.…”
Section: Discussionmentioning
confidence: 77%
“…Even with the administration of therapeutic doses, plasma levels can be altered by deviations in product quality, genetic polymorphism, exaggerated sensitivity of the target tissue, drug interactions, and hepatic and renal dysfunctions. In contrast, no reaction was classified as doubtful, since many are described in the literature and package insert, such as vancomycin and urticarial reaction (Perrin-Lamarre et al, 2010), cisplatin and nephrotoxicity (Yao et al, 2007), carboplatin and anaphylaxis (Iwamoto et al, 2012), bleomycin and Stevens-Johnson syndrome (Giaccone et al, 1986), and etoposide and hypersensitivity reaction (Lindsay, Gaynon, 2012).…”
Section: Discussionmentioning
confidence: 99%